Doing business in Ghana : challenges and opportunities - Spillan, John E.; King, Domfeh Obed (Palgrave Macmillan, 2017)
This book provides a thorough perspective on the realities of doing business in Ghana, outlining the economic, social, technological, and cultural dimensions of the society. It offers insight for entrepreneurs into the region's markets based on GDP growth, political and governmental systems, relationships with investors, and other factors. Considered a beacon of hope for Africa, Ghana is a country with a competitive labor force, stable political environment, and lots of economic opportunities for new business ventures. This book will offer academics a good understanding of the major issues affecting business development in Ghana, and inform students, scholars, managers, and leaders on the paths necessary to pursue launching a product or service in Africa.
Keywords: Ghana -- Economic conditions -- 1979-; New business enterprises -- Ghana.; Corporate culture -- Ghana.; Marketing -- Ghana.; Ghana.; Since 1979; elektronické knihy; electronic books